Development of Middle School Science Learning Module Based on Scientific Literacy on Electrical in Nerve Cells Topic - devi rifdha ristianti (Program Studi Pendidikan IPA, Universitas Lambung Mangkurat, 2023)
Science literacy is a very crucial competency mastered by students in order to play a role in the development of science and technology and society. However, the science literacy of students at the first middle school level is still relatively low. This study aims to analyze the validity and consistency in the Junior High School Science teaching module as well as supporting devices for modules based on scientific literacy of electrical materials in nerve cells. This study used the Tessmer formatting assessment method. Research on the development of this teaching module to the stage of Expert Research Prototyping which is validated by 3 validators. New data collection techniques include teaching module validation, lesson plan validation, student response validation, and learning outcome test validation. Data analysis techniques are descriptive, qualitative and quantitative. As a result of the research shows: 1) validation of teaching modules in the very good category, 2) validation of lesson plans in the very good category, 3) validation of student responses with good value, and 4) validation of good value learning outcomes tests. It was concluded that the Junior High School Science teaching module based on scientific literacy of electrical materials on nerve cells developed is suitable for use in learning.